PLANNING OF RAW MATERIAL INVENTORY TO MAKE TOFU METHOD WITH MATERIAL REQUIRETMENSPLANNING (MRP) - Damayanti; Filia Sari, Rina; Aprilia, Rima; Iman, Nur (Journal of Mathematics and Scientific Computing With Applications, 2022)
UD. Ai Kampung Bilah Tofu Factory, Labuhan Batu Regency is an industry that is engaged in the processing of Tofu. The purpose of this study is to determine the amount of tofu production from forecasting the number of requests for the previous period. Problem with UD. The aim of the Kampung Bilah Tofu Factory is that it has not implemented rules in controlling the supply of raw materials. In the production process, there are often obstacles, namely the use of raw materials and orders that are not appropriate. Optimum planning and inventory of material requirements is carried out using the Material Requirement Planning method. MRP is a method of planning and scheduling better inventory on a product that is produced. In this study the Material Requirement Planning method, the lot sizing technique used is Lot For Lot, Economic Order Quantity, Priode Order Quantity. Based on the calculation results, Material Requirement Planning using the lot sizing technique, namely Lot For Lot, produces a total cost of Rp. 2,640,000 minimum orders for raw materials.